دور الحوكمة المؤسسية في تحسين الأداء الوظيفي بمؤسسات التعليم العالي في الجزائر - بايع راسو حنان (Universty Of El-oued جامعة الوادي, 2025)
الملخص: تهدف هذه الدراسة إلى معرفة واقع مستوى تطبيق مبادئ الحوكمة المؤسسية ودورها في تحسين الأداء الوظيفي بجامعة الوادي، حسب آراء نواب المدير وعمداء الكليات ونوابهم، ورؤساء الأقسام ونوابهم. ولتحقيق أهداف الدراسة من الناحية العلمية، تم الإعتماد على المنهج الوصفي التحليلي، وعلى الاستبانة كأداة رئيسية لجمع البيانات، وتوزيعها على عينة الدراسة (87)مفردة، وباستخدام برنامج الاحصائي (24SPSS). وتوصلت الدراسة إلى نتائج أهمها أن مستوى تطبيق مبادئ الحوكمة المؤسسية في مؤسسات التعليم العالي محل الدراسة كان بدرجة عالية، وأيضا وجود دور للحوكمة المؤسسية (للشفافية والعدالة التنظيمية والمشاركة الفعالة ومساءلة الموظفين) في تحسين الأداء الوظيفي من خلال التأثير المعنوي الإيجابي. Résumé : فرنسية أو انجلزية This study aims to identify the reality of the level of application of corporate governance principles and their role in improving job performance at Al Wadi University, according to the opinions of the vice-chancellors, deans of colleges and their deputies, and heads of departments and their deputies. To achieve the objectives of the study from a scientific perspective, the descriptive analytical approach was adopted, and the questionnaire was used as the main tool for collecting data, and distributing it to the study sample (87) individuals, using the statistical program (24SPSS). The study reached the most important results, the level of application of corporate governance principles in the higher education institutions under study was high, and also the existence of a role for corporate governance (transparency, organizational justice, effective participation and employee accountability) in improving job performance through positive moral influence.
-دراسة حالة جامعة الوادي.
أطروحة دكتوراه تخصص تسيير عمومي في العلوم الاقتصادية والتجارية وعلوم التسيير
Keywords: حوكمة مؤسسية، أداء وظيفي، مؤسسات التعليم العالي; Governance Institutional; Job performance; Institutions of higher educatio